Autonomic Characteristics of Sudden Unexpected Death in Epilepsy in Children—A Systematic Review of Studies and Their Relevance to the Management of Epilepsy in Rett Syndrome - Singh, Jatinder; Lanzarini, Evamaria; Santosh, Paramala (Frontiers in Neurology, 2021)
Aim: To systematically identify and critically appraise studies that investigate the autonomic characteristics of Sudden Unexpected Death in Epilepsy (SUDEP) in the paediatric population. We also wanted to explore how this information would be relevant to the management of epilepsy in patients with Rett Syndrome. Method: Using PRISMA guidelines, a systematic review of PubMed, Scopus, Cochrane, PsycINFO, Embase and Web of Science databases was performed to identify eligible studies. After extracting data from the included studies, a thematic analysis was undertaken to identify emerging themes. A quality appraisal was also done to assess the quality of the included studies. Results: The systematic search revealed 41 records, and 15 full-text articles on the autonomic characteristics of SUDEP in children were included in the final analysis. Following thematic analysis, three themes were identified (I) modulation in sympathovagal tone, (II) pre- and post- ictal autonomic changes and (III) other markers of autonomic dysregulation in children with epilepsy. Modulation in sympathovagal tone emerged as the theme with the highest frequency followed by pre- and post- ictal autonomic changes. While the themes provide additional insight into the management of epilepsy in the Rett syndrome population, the quality of evidence concerning the autonomic characteristics of SUDEP in the paediatric population was low and underscores the importance of much needed research in this area. Conclusion: The mechanism of SUDEP in the paediatric population is complex and involves an interplay between several components of the autonomic nervous system. While direct clinical inferences regarding paediatric SUDEP could not be made, the thematic analysis does suggest that in vulnerable populations such as Rett Syndrome, where there is already a pervasive autonomic dysregulation, pro-active surveillance of the autonomic profile in this patient group would be useful to better manage epilepsy and reduce the SUDEP risk.